Racial and Generational Issues in Competitive Cycle Racing in Durban in the Closing Decades of the Twentieth Century: A Case Study of the Triangle Cycling Club - Waters, Geoff (The Journal of Natal and Zulu history, 2021)
Segregated sport was a source of bitter conflict in apartheid South Africa. This paper focuses on cycle sport in apartheid-era Natal, concentrating on the circumstances which led to the rise and ultimately to the demise of one specific multiracial Durban cycling club: the 'Triangle Cycling Club.' Based on a mixed research methodology, it explores the impact on the micro-level of the state's changing sports policies on local cycle sport over the last quarter of the twentieth century. It examines the effects which these had as they coincided with the sudden unanticipated influx into cycle sport of veteran competitors from endurance sports. It explores the philosophy on which Triangle CC was founded, identifies the sporting achievements of the club's leading members and details the great 'Adventure Tour' to Cape Town in 1991. Finally, it reflects on the demise of the club and of traditional cycle sport in the 1990s as enthusiasm for new forms of cycling such as 'mountain biking' and mass-participation 'sportives' reached new heights.